The Extent to Which Schools with Mechanistic Structures and their Job Characteristics are Likely to Generate Teachers’ Organisational Commitment: Study Conducted in a Private School in Abu Dhabi - Mansour, Hadi (2020)
Organisational structures are basic requirements of all social grouping including organisations such as schools and educational institutions. The decided structure determines the structural components of the organisation such as Centralisation, Specialisation, and Formalisation which in turn directly contribute to the creation of specific balance of job characteristics. Considering these job characteristics, labour motivation and satisfaction begin to develop at varying degrees in the short term meanwhile feeding into the long-term organisational commitment of the staff. The study aims to investigate the effect of mechanistic structures on job characteristics and their combined effect on job satisfaction and organisational commitment. Educational institutions such as high-schools, are by nature bureaucratic and mechanistic in structure therefore develop along strictly formalised and centralised lines with highly specialised job functions. This innate nature of these organisations develops along common job characteristics which may limit the autonomy of its members and influence the diversity of skills used as well as their sense of task significance. Such characteristics further influence the commitment of the teachers towards the organisation; some may have a lack of alternative options in which case they may accept the current status quo while others may truly believe in the organisations objectives and remain with the school because of the shared belief. To investigate the perception of teachers, an international school is utilized as a case study and a survey is conducted. Via the Job Diagnostic Survey (JDS) and Motivational Potential Score (MPS) respondents submit their views to be analysed statistically to determine general opinion. Many teachers do in fact possess affective commitment towards the school yet perceive their roles as severely curtailed in terms of authority and autonomy while limited in their ability to utilize many skills sets due to the extreme specialisation inherent in their roles. It is determined that teachers view the organisation as highly centralised due to the need for bureaucracy and the degrees of specialisation and formalisation are also high. Staff are motivated due to their perception of the importance of their roles however an increase in autonomy and authority in decision making as well as diversifying the job skills used during teaching could further increase motivation. The findings are limited due to the small scale nature of the study and do not take into account the possibility of professional commitment as the source of motivation.